Curriculum development in the Philippine setting - Andres, Tomas Quintin D. (Mandaluyong City, Philippines : National Book Store, 1989)
Education is a force for social disintegration, says a critic in the third world, breaking up cultures and promoting a modernity without significant relationship to the past, to the traditional culture of a people, or even to present realities.
Chapter 1. Principles and theories in curriculum development -- Chapter 2. Curriculum development in the philippines -- Chapter 3. Historical perspective -- Chapter 4. Curriculum approaches -- Chapter 5. Curriculum design -- Chapter 6. Implementation -- Chapter 7. Curriculum evaluation -- Chapter 8. Current trends and issues.
Includes bibliographical references and index.
Keywords: CURRICULUM PLANNING -- STUDY AND TEACHING